Implementasi Logika Dengan Pemrograman Java Netbeans 7.0 - Ramadhan, Hari; Dedi Leman (Universitas Mandiri Bina Prestasi (UMBP), 2024)
Tritech Informatics Vocational School is one of the references for Information Technology and Software Engineering Schools that can train students to hone and develop their knowledge in the field of computers. Here, both state and private universities take part in training and community service activities to help train students at school to hone and develop their knowledge. Through this training and community service activity, students or audiences are expected to be able to increase their knowledge in programming, especially basic algorithm programming. Also, with this training and community service activity, students at Tritech Informatics Vocational School Medan can develop their knowledge in the fields of education and teaching. So that the knowledge gained from this activity can be useful for them in the future. We, from one of the private universities, will provide training and insight into arrays that can be implemented in the Java programming language, where the data structure used to store a certain amount of data is of the same type. We will provide students with Tritech Informatics Vocational School Medan training in the form of Avarage Logic, Summery in an Array. Where this training is intended to hone and develop students' knowledge while implementing the Tridharma Higher Education Program.